Symptomatological frequency of anxiety and depression in nursing students at Universidad Privada Huancayo Franklin Roosevelt-2023 - De la Calle Castro , Indira Anahi (2024)
Objective: To determine the symptomatological frequency of anxiety and depression in nursing students at the Franklin Roosevelt Private University of Huancayo -2023. Material and Methods: The method of this research will be the scientific one which consists of a mainly used research method. The simple descriptive and cross-sectional non-experimental research design, the type of research, according to the purpose carried out, will be basic, the level of research will be descriptive. Results: The results show that 51% of the students of the professional school of nursing had a symptomatological frequency of mild anxiety and 44% did not have anxiety, while 41% of the students had a symptomatological prevalence of mild depression and 59% did not have depression. Conclusion: concluding, the students of the Professional School of Nursing of the Franklin Roosevelt Private University of Huancayo have statistically observed that there is a presence of anxiety and mild depression in our students.